Synthesis of Structurally Diverse 3-, 4-, 5-, and 6-Membered Heterocycles from Diisopropyl Iminomalonates and Soft C-Nucleophiles - Kattamuri, Padmanabha V. (J Org Chem, 2019)
Herein, we present a general synthetic strategy for the preparation of 3-, 4-, 5- and 6-membered heterocyclic unnatural amino acid derivatives by exploiting facile Mannich-type reactions between readily available N-alkyl- and N-aryl-substituted diisopropyl iminomalonates and a wide range of soft anionic C-nucleophiles without using any catalyst or additive. Fully substituted aziridines were obtained in a single step when enolates of α-bromo esters were employed as nucleophiles. Enantiomerically enriched azetidines, γ-lactones and tetrahydroquinolines were obtained via a two-step catalytic asymmetric reduction and cyclization sequence from ketone enolate-derived adducts. Finally, highly substituted γ-lactams were prepared in one pot from adducts obtained using acetonitrile-derived carbanions. Overall, this work clearly demonstrates the utility of iminomalonates as highly versatile building blocks for the practical and scalable synthesis of structurally diverse heterocycles.